THE COMPARISON OF THE EFFICACY OF CEFTRIAXONE AND COMBINATION OF AMPICILLIN-CHLORAMPHENICOL OF CHILDREN WITH PNEUMONIA OF PKU MUHAMMADIYAH HOSPITAL IN BANTUL - Astuti Wulandari, Nur; Darmawan, Endang; Umam Kurniawan, Nurcholid (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
Pneumonia is an infectious disease that occurs in the lungs caused by various microorganisms. Patients of children with pneumonia in Indonesia experienced an increase in 2013. Antibiotics therapy is the main therapy for patients with pneumonia. This study aims to compare of the efficacy of ceftriaxone and combination of ampicillin-chloramphenicol of children with pneumonia of PKU Muhammadiyah hospital in Bantul. The study design was a randomized controlled trial with prospective Open trial do in March 2018 to June 2018. The outcomes used were tightness, cough, retraction, temperature, respiration rate, and length of stay. Research data were analyzed using Chi Square test, Fisher test, independent t test and Mann Whitney test. The results of the study of ceftriaxone (n=26) and ampicillin chloramphenicol groups (n=26) showed that the percentage of patients who had not experienced tightness was 82.7%, not cough 7.7%, and there was no retraction of 76.9% with p<0.05. The mean ±SD temperature of the ceftriaxone group was 36.5±0.12 and the ampicillin chloramphenicol group was 36.57±0.09 with a p<0.05. The mea n±SD respiration rate of the ceftriaxone group was 27.9±3.22 and the ampicillin chloramphenicol group was 27.92±2.62 with a p <0.05. The mean ±SD length of stay in the ceftriaxone group was 4.5±0.81 and the ampicillin chloramphenicol group was 4.26±0.66 with a p<0.05. Conclusions showed that there was no significant difference between the effectiveness of ceftriaxone and ampicillin chloramphenicol on fever, spasms, cough, retraction, temperature, respiration rate and length of stay.